Interim report. - Great Britain. Dominions Royal Commission
Minutes taken in London, Oct. 1912-July 1914, New Zealand in 1913, Australia in 1913, South Africa in 1914, Newfoundland in 1914, Maritime Provinces of Canada in 1914 and Central and Western Provinces of Canada in 1916. Mode of access: Internet.